Effect of DAP (P21%) Fertilizer on Total Saliva officinalis Flavonoid Content - Hassan , Zainab Yaseen Mohammed; Majeed, Suad Mohammed (Iraqi Journal of Science, 2022)
The effect of (Di-Ammonium Phosphate DAP) (P21%), as plant fertilizer on content of the Saliva officinalis. Total flavonoid as an important active constituent was investigated in the present study. Three samples (F1, F2, and F3) of Saliva officinalis were grown in soil treated with DAP (100, 200, and 300) kg/hector respectively. Another two samples were studied: F0 as a plant sample grown in soil untreated with fertilizer and F4 as wild type obtained from market. Total flavonoids were estimated Quantitatively by Rutin standard curve and qualitatively by TLC method in corresponding to standard flavonoids. Results showed that different concentrations of DAP treated soil affected flavonoid contained of the Iraqi cultivated Saliva officinalis in different manner. The lowest flavonoid contained was untreated samples (F0), and the best result was obtained from plant in soil treated with 200kg/H of DAP(f2) when the soil treated with DAP plant fertilizer in concentration (200kg/H) F2 sample.